1997
DOI: 10.1016/s0014-5793(97)01074-0
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroascorbate and dehydroascorbate reductase are phantom indicators of oxidative stress in plants

Abstract: In many physiological studies dehydroascorbate (DHA) reductase is regarded as one of the chloroplast enzymes involved in the protection against oxidative stress. Here, evidence is presented that plant cells do not possess a specific DHA reductase. The DHA reductase activities measured in plant extracts are due to side reactions of proteins containing redoxactive dicysteine sites. Native gel electrophoresis combined with specific activity staining revealed three different proteins with DHA reductase activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 19 publications
1
57
1
3
Order By: Relevance
“…In plants, DHA arises from the dismutation of semi-dehydroascorbate (SDHA), the major oxidized form of ascorbate with SDHA normally recycled back to ascorbate by an NAD(P)H-dependent SDHA reductase (29). However, if SDHA is allowed to accumulate then DHA accumulates, although the importance of this reaction in planta is the subject of some debate (30,31). The isolation of DHARs predicted to be targeted to either the cytosol and chloroplast clarifies the compartmentalization of these enzymes in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, DHA arises from the dismutation of semi-dehydroascorbate (SDHA), the major oxidized form of ascorbate with SDHA normally recycled back to ascorbate by an NAD(P)H-dependent SDHA reductase (29). However, if SDHA is allowed to accumulate then DHA accumulates, although the importance of this reaction in planta is the subject of some debate (30,31). The isolation of DHARs predicted to be targeted to either the cytosol and chloroplast clarifies the compartmentalization of these enzymes in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, kinetic modeling of the chloroplast ascorbate-glutathione pathway suggested that the chemical reaction could be largely predominant (Polle, 2001). For these reasons, the physiological importance of DHARs in oxidative stress has been subject to some debate (Morell et al, 1997;Foyer and Mullineaux, 1998;Smirnoff, 2011), and the biological roles of the endogenous genes, and the relationships between them, remain to be elucidated.…”
mentioning
confidence: 99%
“…(Conklin, 2001;Tokugana, et al, 2005 (Foyer and Halliwell, 1976;Foyer et al, 1983;Shigeoka et al, 2002 (Shigeoka et al, 2002;Shimaoka et al, 2000;Urano et al, 2000;Yoshimura et al, 2000). 이들 효소의 활성변화에 영향을 주는 인자로는 오존처리 , 관수온도 (Kang et al, 2001), 수분부족 (Kang, 2008) 등이 있으며, 시금치 (Morell et al, 1997), 완두콩 (Leterrier et al, 2005), 토마토 (Grantz et al, 1995) )를 측정하였 다 . DHAR (EC 1.8.5.1)의 활성도는 10 mM GSH, 5 mM DHA와 조효소액을 첨가한 50 mM .…”
Section: 아스코브산 (Ascorbic Acid: Vitamine C)은 식물에서 여러 가지 기능을 하는 물질로서 총 unclassified